Liver injury is associated with severe coronavirus disease 2019 (COVID‐19) infection: A systematic review and meta‐analysis of retrospective studies - Parohan, Mohammad; Yaghoubi, Sajad; Seraji, Asal (Hepatology research, 2020)
The coronavirus disease 2019 (COVID‐19) outbreak is a major threat to human beings. Lung injury has been reported as the major outcome of COVID‐19 infection. However, liver damage has also been considered to occur in severe cases. The current meta‐analysis of retrospective studies was carried out to summarize available findings on the association between liver injury and severity of COVID‐19 infection. Online databases including PubMed, Scopus, Web of Science, and Cochrane Library were searched to detect relevant publications up to 1 April 2020, using relevant keywords. To pool data, a fixed‐ or random‐effects model was used depending on the heterogeneity between studies. Furthermore, publication bias test and sensitivity analysis were also applied. In total, 20 retrospective studies with 3428 COVID‐19 infected patients (severe cases, n = 1455; mild cases, n = 1973), were included in this meta‐analysis. Higher serum levels of aspartate aminotransferase (weighted mean difference, 8.84 U/L; 95% confidence interval [CI] 5.97 to 11.71; P < 0.001), alanine aminotransferase (weighted mean difference, 7.35 U/L; 95% CI, 4.77 to 9.93; P < 0.001), total bilirubin (weighted mean difference, 2.30 mmol/L; 95% CI, 1.24 to 3.36; P < 0.001), and lower serum levels of albumin (weighted mean difference, −4.24 g/L; 95% CI, −6.20 to −2.28; P < 0.001) were associated with a significant increase in the severity of COVID‐19 infection. The incidence of liver injury, as assessed by serum analysis (aspartate aminotransferase, alanine aminotransferase, total bilirubin, and albumin levels), seems to be higher in patients with severe COVID‐19 infection.